Application of Wickerhamomyces anomalus in Simulated Solid-State Fermentation for Baijiu Production: Changes of Microbial Community Structure and Flavor Metabolism - Wang, Wenhua; Fan, Guangsen; Li, Xiuting; Fu, Zhilei; Liang, Xin; Sun, Baoguo (Frontiers in Microbiology, 2020)
Wickerhamomyces anomalus is the main species that produces esters in brewing the Chinese liquor Baijiu; esters are crucial for the quality of Baijiu. In this study, simulation solid-state fermentation for Baijiu production was used to explore whether artificial addition of W. anomalus could improve the flavor substance in Baijiu, and the underlying mechanisms. Two experimental groups were studied, in which W. anomalus Y3604 (Group A) and YF1503 (Group B) were added, respectively; in the control group (Group C), no W. anomalus was added. Adding strain Y3604 increased the content of esters in fermentation samples, especially ethyl acetate and ethyl caproate, and reduced the content of higher alcohols. Adding strain YF1503 had little effect on the ester content, but decreased the content of higher alcohols. The diversity and abundance of prokaryotic genera in Group A and B samples were similar, but there were some differences compared with Group C. The correlations of genera in Group A or B samples were simple compared with group C. Although the predominant eukaryotic genera in the three groups were consistent, the abundance of each genes varied between groups. Based on our findings, bioaugmentation of Baijiu fermentation with W. anomalus will change the ethyl acetate content and also cause changes in the levels of other flavor substances. We suggest that the changes in flavor substances caused by the addition of W. anomalus are mainly due to changes in the microbial community structure resulting from the addition of W. anomalus.